The investigation of the possible effects of cholesterol reducing agent simvastatin on rat testis tissue - Ozek, Nihal Simsek; Sara, Yildirim; Onur, Rustu; Yilmaz, Okkes; Severcan, Feride (Biophysical Society, 2007)
[Abstract Not Available]
51st Annual Meeting of the Biophysical-Society -- MAR 03-07, 2007 -- Baltimore, MD